RANTES upregulation in the Alzheimer’s disease brain: a possible neuroprotective role - Tripathy, Debjani (2008)
Numerous studies demonstrate inflammatory proteins in the brain and microcirculation in Alzheimer’s disease (AD) and implicate inflammation in disease pathogenesis. However, emerging literature suggests that neuroinflammation can also be neuroprotective. The chemokine RANTES has been implicated in neurodegenerative diseases including AD. The objectives of this study are to determine the expression of RANTES in AD microvessels, its regulation in endothelial cells and its effects on neuronal survival. Our data show elevated expression of RANTES in the cerebral microcirculation of AD patients. Treatment of neurons in vitro with RANTES results in an increase in cell survival and a neuroprotective effect against the toxicity of thrombin and sodium nitroprusside. Oxidative stress upregulates RANTES expression in rat brain endothelial cells. Developing strategies to augment neuroprotection and diminish inflammatory activation of multifunctional mediators such as RANTES holds promise for the development of novel neuroprotective therapeutics in AD.